Knowledge, Attitude and Use of Information Communication Technology (ICT) Among Teachers at SK LKTP Tenang, Labis, Johor - Abdullah, Mohamad Amir Hamzah; Yaacob, Noorulsadiqin Azbiya (Emerging Advances in Integrated Technology, 2023)
Over the years, the emergence of Information and Communication Technology (ICT) has resulted in significant benefits in the field of education. ICT is used to provide a synchronous and asynchronous teaching and learning platform for both teachers and students. The purpose of this study is to assess teachers’ knowledge, attitudes, and use of information and communication technology at SK LKTP Tenang, Labis, Johor. It was carried out to assist teachers in implementing a variety of ICT supported methods and resources in the classroom to improve the teaching and learning process. Teachers at SK LKTP Tenang, Labis, Johor received a survey questionnaire with five sections. The study’s findings indicate that the study respondents lack sufficient knowledge of how to use ICT. This is because, there are several challenges faced by teachers when implementing ICT in the teaching and learning environment.Over the years, the emergence of Information and Communication Technology (ICT) has resulted in significant benefits in the field of education. ICT is used to provide a synchronous and asynchronous teaching and learning platform for both teachers and students. The purpose of this study is to assess teachers’ knowledge, attitudes, and use of information and communication technology at SK LKTP Tenang, Labis, Johor. It was carried out to assist teachers in implementing a variety of ICT supported methods and resources in the classroom to improve the teaching and learning process. Teachers at SK LKTP Tenang, Labis, Johor received a survey questionnaire with five sections. The study’s findings indicate that the study respondents lack sufficient knowledge of how to use ICT. This is because, there are several challenges faced by teachers when implementing ICT in the teaching and learning environment.